1997
DOI: 10.1038/sj.bjp.0701200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that cyclic AMP phosphodiesterase inhibitors suppress interleukin‐2 release from murine splenocytes by interacting with a ‘low‐affinity’ phosphodiesterase 4 conformer

Abstract: 1 We have investigated the suppressive e ects of rolipram, RP 73401 (piclamilast) and other structurally diverse inhibitors of cyclic AMP-speci®c phosphodiesterase 4 (PDE4) on interleukin (IL)-2 generation from Balb/c mouse splenocytes exposed to the superantigen, Staphylococcocal enterotoxin-A (Staph. A). The purpose was to determine whether their potencies are more closely correlated with inhibition of PDE4 from CTLL cells, against which rolipram displays weak potency (low-a nity PDE4), or displacement of [ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…This is consistent with the finding from saturation analyses that piclamilast binds to both sites with equal affinity. The potency order of PDE4 inhibitors tested in this study was in agreement with the potency orders of these inhibitors reported previously for inhibition of enzyme activity (Schneider et al, 1986;Souness et al, 1997Souness et al, , 1999Saldou et al, 1998 3 H]rolipram binding by non-PDE4 inhibitors was less potent and showed no significant differences between the two radioligands. Consistent with their low binding affinities, these drugs also have been shown to be very poor inhibitors of PDE4 enzymatic activity (Schneider et al, 1986;Souness and Scott, 1993;Makhay et al, 2001).…”
Section: Inhibitor Binding To Pde4 569supporting
confidence: 78%
“…This is consistent with the finding from saturation analyses that piclamilast binds to both sites with equal affinity. The potency order of PDE4 inhibitors tested in this study was in agreement with the potency orders of these inhibitors reported previously for inhibition of enzyme activity (Schneider et al, 1986;Souness et al, 1997Souness et al, , 1999Saldou et al, 1998 3 H]rolipram binding by non-PDE4 inhibitors was less potent and showed no significant differences between the two radioligands. Consistent with their low binding affinities, these drugs also have been shown to be very poor inhibitors of PDE4 enzymatic activity (Schneider et al, 1986;Souness and Scott, 1993;Makhay et al, 2001).…”
Section: Inhibitor Binding To Pde4 569supporting
confidence: 78%
“…interleukin-2) may also be inhibited by cyclic AMP phosphodiesterase inhibitors (Souness et al 1997). In addition, LPS is able to induce the release of endogenous factors such as platelet-activating factor (Doebber et al 1985;Szabo et al 1993b), bradykinin (Fleming et al 1992;Ueno et al 1995) or endothelin (Nakamura et al 1991), which can activate eNOS and then cause the release of NO from the endothelial cell and lead to the early fall in MAP.…”
Section: Discussionmentioning
confidence: 98%
“…The result also excludes the possibility that enhancement of cAMP level in cortical neurons is due to cellular penetration differences of these compounds. In previous studies, the suppressive effects of interleukin-2, interleukin-4, and interleukin-5 release from splenocytes by PDE4 inhibitors were closely correlated with inhibition of PDE4 catalytic activity, but not with inhibition of [ 3 H]rolipram binding (19,20). These differing results may be due to distinct actions of PDE4 inhibitors on interleukin release and proliferation.…”
Section: Considering That [mentioning
confidence: 78%
“…A number of pharmacological activities of PDE4 inhibitors, including emesis (13), gastric acid secretion (14), tracheal relaxation and bronchodilation (15), and inhibition of degranulation of neutrophils (16), show no correlation with the inhibitory potency of PDE4 catalytic activity, but do correlate well with the inhibitory potency to displace [ 3 H]rolipram binding. On the other hand, inhibition of superoxide production from eosinophils (17); cAMP accumulation and inhibition of TNFα production from monocytes (16,18); and suppression of interleukin-2, interleukin-4, and interleukin-5 release from splenocytes (19,20) are correlated with the inhibitory potency of PDE4 catalytic activity. These reports suggest that the two conformers of PDE4 are expressed in cells, and inhibition of either conformer via PDE4 inhibitors results in elevation of cAMP.…”
Section: +mentioning
confidence: 99%